Impact of Patient Safety Culture and Reporting Flow Perception on Nurses’ Intentions to Report Safety Incidents - Krissadi, Lovi; Supriyantoro, Supriyantoro (Jurnal Indonesia Sosial Sains, 2024)
The nursing unit accounts for the highest number of Patient Safety Incidents (PSI), with 64.83% of incidents in Hospital X Malang occurring in this unit, creating opportunities for underreporting. This study analyzes the influence of patient safety culture on nurses' willingness to report incidents using a descriptive quantitative cross-sectional approach with Partial Least Square analysis. Data were collected through questionnaires from nurses in various units. Results showed a moderate safety culture and reporting willingness, with significant effects of safety culture on perceptions of reporting flow, which in turn influenced reporting willingness. Weaknesses were found in understanding report-making and grading implementation. The study emphasizes fostering a strong patient safety culture and streamlining reporting systems. Practical applications include targeted training for nurses, enhanced communication channels, and a non-punitive reporting framework to reduce underreporting, strengthen reporting systems, and improve patient safety.